IMPLEMENTASI ALGORITMA K-MEANS CLUSTERING UNTUK MENENTUKAN STRATEGI MARKETING PRESIDENT UNIVERSITY - Johan Oscar Ong (Department of Industrial Engineering Universitas Muhammadiyah Surakarta, 2013)
Information technology advances very rapidly at this time to generate thousands or even millions of data from various aspect of life. However, what can be done with that much data?. In this research, we start from calculation of data set of students who have graduated from President University using k-means clustering algorithm, namely by classifying the data of students into several clusters based on the characteristics of this data in order to discover the information hidden from the data set of student who have graduated from President University. The attribute data that is used in this study is hometown, major and GPA. The purpose of this study is to help the President University's marketing department in predicting promotion strategies undertaken in the cities in Indonesia. Information gained in this study can be used as a references in determining the proper strategy for marketing team in their promotion activities in the cities in Indonesia so that the campaign will be more effective and efficient.